A journey mapping study of healthcare professionals’ involvement in fertility preservation for cancer patients - Di Xue; Aijun Zhu; Hongyuan Song; Meijuan Cheng; Zhenhua Lu; Huaijie Yang (Frontiers in Oncology, 2026)
Objective Based on journey mapping, this study aimed to identify the main tasks, key pain points, and emotional experiences of healthcare professionals throughout their involvement in fertility preservation for cancer patients, and to provide evidence for designing targeted interventions and optimizing fertility preservation services. Methods This qualitative study adopted purposive sampling to recruit 24 healthcare professionals from the departments of breast and thyroid surgery, oncology, and related departments at Yichang Central People’s Hospital between June and August 2025. Semi-structured interviews were conducted, and thematic analysis guided data coding and analysis. A journey map was then constructed. Results The journey map of healthcare professionals’ engagement in cancer patients’ fertility preservation consisted of four stages: needs identification and topic communication, option assessment and referral, intervention and treatment, and long-term follow-up. Analysis of the interview data yielded 14 themes. The key pain points included insufficient knowledge, ambiguous role perception, the sensitivity of reproductive discussions, constrained medical resources, inadequate multidisciplinary collaboration, and gaps in follow-up care. Conclusion Healthcare professionals acknowledge the importance of fertility preservation for cancer patients, yet they encounter multiple obstacles in clinical practice, such as deficiencies in professional knowledge and skills, weak interdisciplinary collaboration, and limitations in resources and policies. A multilevel intervention strategy should be developed through measures such as creating standardized assessment tools, building regional collaborative networks, strengthening knowledge and skill training with clear role definitions, improving cross-departmental information sharing, and prioritizing follow-up care. These efforts can enhance healthcare professionals’ engagement in fertility preservation and improve the quality of survival for cancer patients.